Endoscopic posterior decompression of lumbar canal stenosis - Yadav, Yad Ram; Yadav, Nishtha; Parihar, Vijay; Kher, Yatin; Ratre, Shailendra (Indian Journal of Neurosurgery, 2013)
Lumbar canal stenosis (LCS) is quite common. Surgery is indicated when patient fails to improve after conservative treatment. Endoscopic technique can be used in LCS and lateral recess stenosis. It can be performed in degenerative canal stenosis or with disc bulges. Bilateral severe bony canal stenosis and unstable spine are the contraindications. This procedure should be avoided in patients with a history of trauma. Detailed history and thorough physical examination should be performed to find out exact level of pathology responsible for symptoms. Patient’s symptoms must correlate with radiological findings. Magnetic resonance imaging is the investigation of choice because of its superior visualization of soft-tissue. Computed tomography scan does give a more accurate and detailed picture of the bony anatomy. Although the operative time and the complication rate could be more in the initial learning curve, the results of endoscopic decompression are comparable with conventional open procedures with the additional benefit of decreased complications and lower morbidity, when sufficient experience is gained. Complications in endoscopic surgery for LCS could be dural tears, hematomas and root and facet injury. This procedure is also associated with limitations such as steep learning curve and the contra lateral decompression may not be as good as ipsilateral side. Some of the limitations of this technique can be overcome by attending live operative workshop, practice on models and hands on cadaveric dissection. Conversion to an open procedure may be required when there is disorientation, management of dural tear and for control of bleeding.
Keywords: Endoscopic surgical procedure; endoscopy; lumbar disc disease; spinal canal; spinal endoscopy; spinal stenosis; surgical endoscopy